Self‐reported food intolerances in an Indian population: Need for individualization rather than a universal low‐FODMAP diet - Abraham, Philip; Dhoble, Pavan; Desai, Devendra; Joshi, Anand; Gupta, Tarun (JGH open, 2023)
Background and Aim Low‐fermentable oligo‐, di‐, and monosaccharides and polyol (FODMAP) diets have been recommended for individuals with food intolerance and irritable bowel syndrome (IBS). Individual food intolerances may, however, not correspond to the FODMAP content alone. Methods We conducted a survey on self‐reported intolerance to articles of food commonly identified as high FODMAP in 400 healthy Indian subjects (median age 40 years; 69% men) and 204 consecutive consenting patients with IBS (median age 36 years; 58% men). Results One‐hundred seventy‐nine (44.8%) healthy subjects and 147 (72.1%) patients with IBS reported some food intolerance (P < 0.00001); the latter reported intolerance to all items (except nuts) more frequently than healthy subjects. The prevalence, however, varied from 2.5 to 32%. Milk intolerance was reported equally commonly by healthy subjects and patients (23% vs 29.9%). Twenty‐three (11.3%) patients and no healthy subjects reported wheat sensitivity. The IBS diarrhea subgroup reported intolerance to milk, pulses, capsicum, cauliflower, leafy vegetables, and dry fruits more frequently than the constipation subgroup. Conclusion From among a list of high‐FODMAP items, individuals' intolerance varied widely, suggesting that individuals should be the final judge in deciding their elimination diets rather than devise them based on the FODMAP content alone. As in the West, food intolerance was reported more commonly by patients with IBS, especially those with diarrhea, than by healthy individuals. Also noteworthy is the low prevalence of milk intolerance in a subcontinent labeled as high in lactose intolerance. Unlike in the West, wheat intolerance was not reported by any healthy individual. Individual food intolerances may not correspond to the fermentable oligo‐, di‐, and monosaccharides and polyol (FODMAP) content alone. From among a list of high‐FODMAP items, individuals' intolerance varied widely, suggesting that individuals should be the final judge in deciding their elimination diets rather than devise them based on FODMAP content alone.